Glyphosate escalates horizontal transfer of conjugative plasmid harboring antibiotic resistance genes. Issue 1 (1st January 2021) - Zhang, Hongna; Liu, Jingbo; Wang, Lei; Zhai, Zhenzhen
ABSTRACT: Glyphosate has been frequently detected in water environments because of the wide use for controlling weed in farm lands and urban areas. Presently, the focus of the majority of studies is placed on the toxicity of glyphosate on humans and animals. However, the effects of glyphosate on horizontal transfer of conjugative plasmid carrying antibiotic resistance gene (ARG) are largely unknown. Here, we explored the ability and potential mechanism of glyphosate for accelerating horizontal transfer of conjugative plasmid-mediated ARG. The results showed that glyphosate can effectively boost horizontal transfer rate of conjugative plasmid carrying ARG. The possible mechanism analysis demonstrated that over-production of reactive oxygen species and reactive nitrogen species effectively regulated expression levels of bacterial outer membrane protein and conjugative transfer-related genes, thereby resulting into elevated horizontal transfer rate of plasmid-mediated ARG. In conclusion, this study casts new understanding into the biological effects of glyphosate on ARG. GRAPHICAL ABSTRACT: uf0001